2005
DOI: 10.4103/0970-4388.16881
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dental caries in Turkish preschool children

Abstract: The aim of this study was to evaluate risk factors of dental caries in preschool children in Istanbul. Five nursery schools in Istanbul were included and results of 598 students' were collected. Subjects were orally examined. Socio-demographic data were obtained from the records and from parents. Oral examination data were recorded on examination forms in accordance with the WHO criteria. Bivariate analyses were conducted using chi-square test Multivariate analyses were then performed to estimate the simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
14
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
6
14
2
9
Order By: Relevance
“…Previous studies have reported conflicting results showing some [Chu et al, 1999] or no effect [Namal et al, 2005]. It is possible that the different results are related to the differences in the prevalence of toothbrushing in the studied populations.…”
Section: Discussioncontrasting
confidence: 38%
“…Previous studies have reported conflicting results showing some [Chu et al, 1999] or no effect [Namal et al, 2005]. It is possible that the different results are related to the differences in the prevalence of toothbrushing in the studied populations.…”
Section: Discussioncontrasting
confidence: 38%
“…A similar relationship between plaque levels of Streptococcus mutans and caries has also been found [17, 27, 2931]. A longer prospective study has also recently reported the most significant predictors of caries at 3–5 years to be Streptococcus mutans [32]. …”
Section: Discussionsupporting
confidence: 65%
“…In Turkey, most studies have focused on the risk factors for early childhood caries and its behavioral, clinical and microbiological determinants [6-9]. No studies have been reported in the literature concerning the impact of dental caries on oral health related quality life (OHRQOL) in preschool children, although a high prevalence of dental caries in childhood has been described in the literature [4,5].…”
Section: Introductionmentioning
confidence: 99%